Conjugated microporous polymers incorporating Thiazolo[5,4-d]thiazole moieties for Sunlight-Driven hydrogen production from water - Mohamed Samy, Maha; Mekhemer, Islam M.A.; Mohamed, Mohamed Gamal; Hammad Elsayed, Mohamed; Lin, Kun-Han; Chen, Yi-Kuan; Wu, Tien-Lin; Chou, Ho-Hsiu; Kuo, Shiao-Wei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
[Display omitted] •Donor–acceptor systems based on conjugated microporous polymers incorporating thiazolo[5,4-d]thiazole linkages was designed.•The integration of electron-rich pyrene and electron-deficient ThTh units in Py-ThTh-CMP provided a H2 evolution rate of 1873 µmol g–1h−1.•A new approach for preparing highly efficient photocatalysts in the quest for the practical development of cost-effective H2 evolution. In this paper, we describe efficient, inexpensive, and donor–acceptor (D–A) systems based on conjugated microporous polymers incorporating thiazolo[5,4-d]thiazole (ThTh) linkages for the extraction of H2 from H2O under visible light in the presence of ascorbic acid (AA) as a sacrificial electron donor without additional noble metals as co-catalyst. The integration of electron-rich pyrene (Py) and electron-deficient ThTh units in Py-ThTh-CMP resulted in a D–A system that provided an H2 evolution rate (HER) of 1874 µmol g–1h−1; this value was greater than those of the other tested CMPs prepared with and without the ThTh acceptor moiety. Notably, Py-ThTh-CMP also exceeded the HERs of many other reported materials for photocatalytic H2O reduction, including co-catalysts based on covalent organic frameworks, CMPs, and graphitic carbon nitride. The DFT and TD-DFT suggested the incorporation of ThTh moiety in the CMPs backbone to enhance the charge transfer via S1 ↔ T1 and contribute to the H2 formation. This study presents a new approach for preparing highly efficient photocatalysts for the practical development of cost-effective H2 evolution.